THE SYNTHESIS AND ELECTROCHEMISTRY OF A NOVEL FERROCENE BIS-PORPHYRIN MOLECULE - Beer, P; Kurek, S (1987)
The synthesis and electrochemistry of a new ferrocene bis-porphyrin molecule (3) derived from 1,1′-bis(chlorocarbonyl)ferrocene and 5-(p-hydroxyphenyl)-10,15,20-triphenylporphyrin are reported. High field 1H NMR data indicate the respective porphyrin macrocyclic rings of 3 are in a gauche type conformation. © 1987.